An early trial of catheter removal after transurethral resection of the prostate at Sindh Institute of Urology and Transplant. - Ali, Syed Wajid; Jan Hafiz, Asad Ullah; Muhammad , Ashhad Ullah Khalil; Khalid, Sana (International Journal of Endorsing Health Science Research, 2022)
Background: Transurethral resection of the prostate gland (TURP) is considered a gold standard in Benign Prostatic Hypertrophy. This study aimed to determine the effectiveness of early catheter removals at 48 hours after TURP in patients with mild to moderate enlargement of the prostate. Methodology: A single interventional study was conducted on 79 male subjects with mild to moderate prostate enlargement, and moderate to severe lower urinary tract symptoms. The outcome was measured six hours after trial without a catheter. Results: The mean age of participants was 64.9 ± 7.8 years, and the mean size of the prostate was 54.8 ± 5.9 gm. The frequency of procedural success was 91% (72) and patients with age < 60 years, 24(96%) had procedural success compared to 48(88.9%) age ≥ 60 years. Conclusion: Early catheter removal trial was found successful in most of the study participants at 48 hours after TURP.